Chromosomal inversions effect body size and shape in different breeding resources in Drosophila buzzatii - Fernández Iriarte, P.J. (2003)
The cactophilic Drosophila buzzatii provides an excellent model for the study of reaction norms across discrete environments because it breeds on rotting tissues (rots) of very different cactus species. Here we test the possible effects of second chromosome inversions on body size and shape (wing loading) across suitable natural breeding substrates. Using homokaryotypic stocks derived from several lines homozygous for four naturally occurring chromosomal inversions, we show that arrangements significantty affect size-related traits and wing loading. In addition, karyotypes show differing effects, across natural breeding resources, for wing loading. The 2st and 2jz3 arrangements decrease and the 2j arrangement increases wing loading. For thorax length and wing loading, karyotypic correlations across host plants are slightly lower in females than in males. These results support the hypothesis that these traits have a genetic basis associated with the inversion polymorphism.